A Comprehensive Review and Meta-Analysis of Spontaneous Brainstem Haemorrhage: Diagnosis and Management Over the Last 25 Years - Nahar, Shashank; Agrawal, Pavni (Nepal Journal of Neuroscience, 2025)
Introduction: Spontaneous brainstem haemorrhage (SBH) is a rare but life-threatening subtype of intracerebral haemorrhage (ICH) that carries high mortality and morbidity rates. Given the brainstem's critical role in vital functions, rapid diagnosis and appropriate management are essential for improving outcomes.Objective: This systemic review aims to comprehensively analyse the definition, diagnostic modalities, and management options for spontaneous brainstem haemorrhage using evidence from studies published over the past 25 years.Methods: A systematic search of PubMed, Scopus, and Cochrane Library databases was conducted for studies published between 1999 and 2024. Inclusion criteria encompassed studies focusing on spontaneous brainstem haemorrhage, its diagnosis, and management strategies. Data were extracted, analysed, and synthesized into tables summarizing diagnostic modalities and treatment outcomes. A meta-analysis was performed where applicable.Results: Advances in neuroimaging, particularly computed tomography (CT) and magnetic resonance imaging (MRI), have significantly improved the early diagnosis of SBH. Management primarily focuses on controlling blood pressure, optimizing neurocritical care, and addressing anticoagulation. While surgical options are limited due to the brainstem's sensitive anatomy, emerging minimally invasive procedures show promise. Mortality rates remain high, ranging from 30% to 70%, with functional recovery being poor in a significant proportion of patients.Conclusion: Spontaneous brainstem haemorrhage remains a challenging neurological emergency with high mortality and poor functional outcomes. While medical management remains the cornerstone, ongoing advancements in neuroimaging and minimally invasive techniques offer hope for improved outcomes. Further research is needed to develop standardized treatment protocols and assess the efficacy of emerging therapies